Comparison of Designer’s Design Thinking Modes in Digital and Traditional Sketches - Wu, Jun-Chieh; Chen, Cheng-Chi; Chen, Hsin-Chia (Design and Technology Education: An International Journal, 2012)
The internal design thinking behaviour of designers in the concept development has been an important issue of cognitive psychology. In this study, the design thinking process designers have in applying digital media and traditional paper in the early concept development stage was explored. Special focus was made on the structure and procedure of problem solving. With the verbal data obtained, the protocol analysis was employed to analyse designer’s thinking behaviours in using different media. From the study, the author had reached the following conclusions: (1) The proficiency and related knowledge designers have for the design project has a big impact on the construction of the design problem and the efficiency of problem solving and completeness of detail design. (2) Compared with the traditional way of idea development, digital media makes it possible for designers to have an indepth description of the detail design with the help of related functions in digital media. (3) Designers can have an effective thinking process regarding the micro and macro aspects of a design project because of the function of software, enhancing the completeness of the design thinking while in traditional pen and paper environment, designers use the synthetic and contrast way to manipulate their idea development. The results obtained in this study will benefit both the design education and practical design activity where digital media is applied.